2023
DOI: 10.3164/jcbn.22-100
|View full text |Cite
|
Sign up to set email alerts
|

SMOC2 promoted vascular smooth muscle cell proliferation, migration, and extracellular matrix degradation by activating BMP/TGF‐β1 signaling pathway

Xiaowei Wang,
Meng Wang,
Zhongxiao Zhou
et al.

Abstract: A widespread degenerative condition of the aorta, abdominal aortic aneurysm (AAA), severely endangers the health of middle-aged and elderly people. SPARC related modular calcium binding2 (SMOC2) is upregulated in the carotid arteries of rats with atherosclerotic lesions, but its function in AAA is still unknown. Therefore, the aim of this research was to evaluate the function of SMOC2 in AAA. The results showed that in the AAA tissues, SMOC2 expression was upregulated compared with healthy controls. Overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Prior extensive in vivo studies have substantiated the essential role of SMOC2 in root dentin formation [28][29][30][31][32]. Additionally, in vitro analyses have underscored the intricate interactions between SMOC2 and signaling molecules such as transforming growth factor-β1, Runx2, and bone morphogenetic proteins, pivotal for odonto/osteogenic differentiation [33,52]. Furthermore, pronounced expression of SMOC2 in the apical papilla growing region of developing mouse and human teeth, followed by a decrease in expression in adult teeth, has been reported [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Prior extensive in vivo studies have substantiated the essential role of SMOC2 in root dentin formation [28][29][30][31][32]. Additionally, in vitro analyses have underscored the intricate interactions between SMOC2 and signaling molecules such as transforming growth factor-β1, Runx2, and bone morphogenetic proteins, pivotal for odonto/osteogenic differentiation [33,52]. Furthermore, pronounced expression of SMOC2 in the apical papilla growing region of developing mouse and human teeth, followed by a decrease in expression in adult teeth, has been reported [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mouse studies have demonstrated that SMOC2 knockdown can ameliorate cardiac function impairment and cardiac fibrosis, potentially through the inhibition of the ILK/p38 signaling pathway 34 . Furthermore, the overexpression of SMOC2 has been observed to enhance vascular smooth muscle cell proliferation, migration, and extracellular matrix breakdown, pointing to its significant role in cardiovascular pathophysiology 35 .…”
Section: Discussionmentioning
confidence: 99%